International Days of Statistics and Economics 2019 2019
DOI: 10.18267/pr.2019.los.186.15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship Between Unemployment Rate, Education Level and Selected Economic Indicators in the Czech Republic 2005-2017

Abstract: Humanitarian workers operate in complex environments with various challenges and demanding working conditions. These challenges put aid workers in a range of risks and under the pressure. However, human resources are crucial for success of humanitarian operations in general. At the same time, each humanitarian operation is reliant on logistics and logistics activities are always connected with logistic staff. Understanding what motivates logisticians to join the humanitarian sector is essential information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The comprehensive work intensity analysis provided in this paper is important because also other degrees of work intensity may be associated with poverty and social exclusion (Kis andGábos, 2016, Kalinowski, 2018). Social policies should then be targeted at persons with reduced work intensity, as confirmed by Blatná (2018). Based on the analysis of the share of people living in households with very low work intensity in the Czech Republic in the period 2005-2016, that study found that the growth in social benefits and increase in the proportion of people in lifelong education leads to a reduction of the proportion of people living in (quasi)jobless households.…”
Section: Discussionmentioning
confidence: 93%
“…The comprehensive work intensity analysis provided in this paper is important because also other degrees of work intensity may be associated with poverty and social exclusion (Kis andGábos, 2016, Kalinowski, 2018). Social policies should then be targeted at persons with reduced work intensity, as confirmed by Blatná (2018). Based on the analysis of the share of people living in households with very low work intensity in the Czech Republic in the period 2005-2016, that study found that the growth in social benefits and increase in the proportion of people in lifelong education leads to a reduction of the proportion of people living in (quasi)jobless households.…”
Section: Discussionmentioning
confidence: 93%